Dealing with Elusive Futures : University Graduates in Urban Africa - Engeler, Michelle; Macamo, Elísio; Steuer, Noemi (Kultur und soziale Praxis, 2018)
The time to come - as well as the exploration thereof - remains elusive for social actors and social scientists alike. The contributors accept the challenge to depict young men and women's future-creating activities in urban contexts of sub-Saharan Africa. Very consciously, they study young graduates having obtained a university degree and provide a vivid picture of their strategies to socially grow older by doing adulthood in contexts of great uncertainty. The examples include Burkina Faso, Guinea, Ethiopia, Mali and Tanzania, visually enriched through pictures taken by young Malian photographers.